Enhancing Online Food Delivery Systems through Comprehensive Text Analytics and Strategic Data Integration - Surabani, Santorini (International Journal of Information Technology and Computer Science Applications, 2024)
Addressing challenges in the online food delivery system involves employing various data analytics techniques. Text Analytics, encompassing web analytics, social media analytics, stream analytics, and geospatial analytics, plays a pivotal role in managing and extracting valuable insights. The use of third-party systems by many companies to meet the demand for online food delivery presents issues related to control. Furthermore, information overload and poorly organized data contribute to observed problems. This research proposes effective data integration as a solution, facilitating strategic analytics for optimal system performance. Proper data sorting enables adaptive planning and priority shifts tailored to customer satisfaction. The framework of data integration is crucial in illustrating the comprehensive analysis of online food delivery systems. The report also delves into the challenges associated with implementing text analytics.